Islamic microfinance in Malaysia: issues and challenges - Kassim, Salina; Kassim, Siti Nadhirah; Othman, Nadhrah (2018)
In many countries, microfinance has been proven to be an effective tool to ena-ble the low income segment of the society to borrow and kick start small busi-nesses. There are three important microfinance institutions in Malaysia, namely Amanah Ikhtiar Malaysia (AIM), Yayasan Usaha Maju (YUM) and Tabung Ekonomi Kumpulan Usahawan Niaga (TEKUN). In accordance to Islamic law, any element of usury must be avoided entirely in economic transactions, hence resulting in the imposition of management fees on the borrowers instead of inter-est. This paper seeks to study the issues and challenges faced by Islamic micro-finance institutions in the Malaysian context.